Characterization and statistical optimization of biosurfactant production using Bacillus subtilis isolated from automotive oil-contaminated soil in Yola, Nigeria - Ja'afaru, Mohammed Inuwa; Abbas, Tema; Ajunwa, Obinna Markraphael; Olaifa, Kayode (Scientific African, 2022)
The need for cost effective and ecofriendly means of producing compounds of environmental, industrial, and other biotechnological applications cannot be overemphasized. Biosurfactant from microbial sources have been identified to have the potential to substitute chemical types. This has led to the continuous bioprospecting for biosurfactant-producing microorganisms and optimization of processes for high yield biosurfactant production. Despite the widespread, high levels of oil-induced soil pollution in Yola, Nigeria and its environs, there is dearth of information on the potential application of indigenous bacteria for biosurfactant production. In this study, a Bacillus subtilis B3 strain was isolated from an automotive oil-contaminated soil in Yola, and was further used for production, characterization, and optimization of biosurfactant activity. The partially purified biosurfactant had a structural elucidation of a lipopeptide and exhibited surface tension reduction of distilled water from 72 to 29.30 mN/m. It also forms stable emulsions between pH 6-8 and temperature 60-80 °C, and a critical micelle concentration of 0.65 %. The dry weight of the purified biosurfactant was 0.25 g/L representing a 1.6-fold increase in comparison with one obtained from conventional medium with 0.16 g/L biosurfactant yield. This finding suggests that the bacterial strain isolated in this study has the potential to meet the demand for bioremediation and other industrial exploitations.